High-performance computing and geography: developments, issues, and case studies. - Turon, I.; Openshaw, Stan (Environment & Planning A, 1998)
Part of a special section on geocomputation, which is defined as the process of applying computing technology to geographical problems. The writers present some of the findings obtained by applying a Cray T3D parallel supercomputer to human geography problems. They stress the fundamental importance of high-performance computing (HPC) as a future pertinent paradigm for doing geography. They provide an introduction to recent developments and demonstrate how new computational intelligence technologies can begin to be used to make the most of opportunities created by data riches from geographic information systems, artificial intelligence tools, and HPC in geography.